Conference reports: Transactions and Connections: Memories of the Past in the European Context. - Cruz-Rus, Celia; Martín-González, Juan José (ESSE, 2014)
This report provides an analysis of the the international seminar “Transactions and Connections: Memories of the Past in the European Context”, held at the University of Málaga in October 2013. The seminar brought together scholars from Spain, Italy, and the UK to explore literary representations of the past. Papers ranged across historical periods, focusing particularly on Enlightenment, the nineteenth century, and contemporary reimaginings of past events. Key themes included memory as a political tool, the influence of early novelistic forms, and the literary recovery of marginalized voices in colonial and gendered contexts. Special attention was given to neo-Victorian fiction, with several presentations analyzing the reinterpretation of Victorian science, criminal history, and cultural myths. Prominent keynote lectures by Sally Shuttleworth and Ann Heilmann addressed sanitary science and women's roles in Victorian divorce trials. The seminar also explored postmodern biofiction, representations of the First and Second World Wars, and the legacy of 9/11, with discussions on trauma, subjectivity, and islamophobia. Overall, the seminar offered rich interdisciplinary insights and emphasized the ongoing literary fascination with the past, its reinterpretation in contemporary narratives, and its implications for identity, ethics, and collective memory.
Dear Juan José (and Rosario), According to the editorial code of The ESSE Messenger, you are given permission to include the publication in RIUMA taking the following into account: "If ESSE receives any request to reproduce material first published in The Messenger, the request will be forwarded to the original author, and if the author agrees to reproduction no objection will be raised by ESSE, provided proper acknowledgement of the original publication is made. ESSE will normally ask the following text to accompany republished material: “Copyright ESSE and [Author’s Name]. First published in The ESSE Messenger XX/Y 20ZZ”. I hope this is OK. Please, let me know if something is not clear. Kind regards, Laura
Keywords: Literatura - Congresos; Novela histórica - Congresos; Conference report; Past; Historical fiction